2021
DOI: 10.1007/s00401-020-02255-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathological consensus criteria for the evaluation of Lewy pathology in post-mortem brains: a multi-centre study

Abstract: Currently, the neuropathological diagnosis of Lewy body disease (LBD) may be stated according to several staging systems, which include the Braak Lewy body stages (Braak), the consensus criteria by McKeith and colleagues (McKeith), the modified McKeith system by Leverenz and colleagues (Leverenz), and the Unified Staging System by Beach and colleagues (Beach). All of these systems use semi-quantitative scoring (4- or 5-tier scales) of Lewy pathology (LP; i.e., Lewy bodies and Lewy neurites) in defined cortical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
150
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 148 publications
(153 citation statements)
references
References 31 publications
(68 reference statements)
1
150
0
2
Order By: Relevance
“…[ 6 ] Furthermore, Lewy pathology (i.e. Lewy bodies and Lewy neurites) was scored using the most recent LP consensus criteria [ 9 ]. For each individual, a tissue block of cortical grey matter from the anterior cingulate was sectioned at 80 µm thickness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 6 ] Furthermore, Lewy pathology (i.e. Lewy bodies and Lewy neurites) was scored using the most recent LP consensus criteria [ 9 ]. For each individual, a tissue block of cortical grey matter from the anterior cingulate was sectioned at 80 µm thickness.…”
Section: Methodsmentioning
confidence: 99%
“…The severity of α-synuclein pathology in the anterior cingulate was graded semi-quantitatively from 0 to 3 based on the validated scoring system from Alafuzoff et al [6] Furthermore, Lewy pathology (i.e. Lewy bodies and Lewy neurites) was scored using the most recent LP consensus criteria [9]. For each individual, a tissue block of cortical grey matter from the anterior cingulate was sectioned at 80 µm thickness.…”
Section: Sample Selectionmentioning
confidence: 99%
“…In Lewy body diseases, including Parkinson’s disease (PD) and dementia with Lewy bodies (DLB), alpha-synuclein accumulates intraneuronally in the central and peripheral nervous systems [ 1 , 3 , 8 ]. Recent studies [ 3 , 6 ] have suggested that spread of alpha-synuclein positive Lewy-related pathology (LRP) follows two distinct patterns—caudo-rostral progression and an amygdala-based progression, the latter usually seen together with Alzheimer’s disease (AD) pathology [ 6 ].…”
mentioning
confidence: 99%
“…DLB was defined as dementia occurring either at presentation or within 1 year of the onset of parkinsonism, with a brain distribution of α-synuclein pathology meeting DLB Consortium criteria for “intermediate” or “high” likelihood [ 70 ]. The Unified Staging System and McKeith criteria received good inter-rater reliability scores in a multi-centre comprehensive analysis defining consensus criteria for the evaluation of Lewy body pathology in post mortem brains [ 6 ]. Three out of 10 DLB cases were additionally diagnosed with AD, due to intermediate or high AD neuropathological changes according to [ 21 ].…”
Section: Methodsmentioning
confidence: 99%